Act and certificate of Annie E. Dixson - Dixon, Annie E.
Act granting pension to Dixson, widow of Henry T. Dixon, formerly a major and assistant paymaster in the U.S. Army, and certificate of approval of the pension.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dixon, Henry T; Military pensions -- United States